2021
DOI: 10.1002/smll.202103307
|View full text |Cite
|
Sign up to set email alerts
|

Bi‐Functional Fe3O4/Au/CoFe‐LDH Sandwich‐Structured Electrocatalyst for Asymmetrical Electrolyzer with Low Operation Voltage

Abstract: The reduction of the overall electrolysis potential to produce hydrogen is a critical target for fabricating applicable hydrogen evolution cells. Sandwich‐structured Fe3O4/Au/CoFe‐LDH is synthesized via a spontaneous galvanic displacement reaction. A series of structural characterizations indicate the successful synthesis of sandwich‐structured Fe3O4/Au/CoFe‐LDH electrocatalyst. The trace amount of Au laying between Fe3O4 and CoFe‐LDH significantly improves the intrinsic conductivity and catalytic activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 65 publications
0
27
0
Order By: Relevance
“…The results indicated that Pd transferred electrons to Co and Fe in the LDH support, which was evidence of the strong interaction of Pd nanoparticles with the LDH substrate. Besides, four distinct components could be seen in the O 1s spectra for Co 1 Fe 3 –LDH/NF and Pd/Co 1 Fe 3 –LDH/NF (Figure d), including the peak located at around 530.2 eV corresponding to oxygen vacancy (V O ), the peak located at around 530.9 eV appertaining to M–O (M = Pd, Co, Fe), the peak at around 531.6 eV belonging to absorbed H 2 O, and the peak at 532.8 eV corresponding to CO 3 2– , which well matched with those reported LDH materials containing interlayer carbonate anions . The relative area ratios of V O to M–O to H 2 O were about 0.21:1.16:1 for Pd/Co 1 Fe 3 –LDH/NF and 0.35:0.92:1 for Co 1 Fe 3 –LDH/NF, proving that Pd nanoparticles anchored on Co 1 Fe 3 –LDH via O atoms and V O sites.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…The results indicated that Pd transferred electrons to Co and Fe in the LDH support, which was evidence of the strong interaction of Pd nanoparticles with the LDH substrate. Besides, four distinct components could be seen in the O 1s spectra for Co 1 Fe 3 –LDH/NF and Pd/Co 1 Fe 3 –LDH/NF (Figure d), including the peak located at around 530.2 eV corresponding to oxygen vacancy (V O ), the peak located at around 530.9 eV appertaining to M–O (M = Pd, Co, Fe), the peak at around 531.6 eV belonging to absorbed H 2 O, and the peak at 532.8 eV corresponding to CO 3 2– , which well matched with those reported LDH materials containing interlayer carbonate anions . The relative area ratios of V O to M–O to H 2 O were about 0.21:1.16:1 for Pd/Co 1 Fe 3 –LDH/NF and 0.35:0.92:1 for Co 1 Fe 3 –LDH/NF, proving that Pd nanoparticles anchored on Co 1 Fe 3 –LDH via O atoms and V O sites.…”
Section: Resultsmentioning
confidence: 54%
“…Pd/Co 1 Fe 3 –LDH/NF and Co 1 Fe 3 –LDH/NF both detected two regions of Co 2p 3/2 and Co 2p 1/2 with their corresponding satellite peaks (Figure b). , In addition, the relative area ratios of Co 2+ to Co 3+ were about 1:0.54 for Pd/Co 1 Fe 3 –LDH/NF and 1:1.08 for Co 1 Fe 3 –LDH/NF, suggesting the reduction of Co species after loading Pd onto Co 1 Fe 3 –LDH/NF. Similarly, the Fe 2p spectra showed two regions of Fe 2p 3/2 and Fe 2p 1/2 with their corresponding satellite peaks from both Pd/Co 1 Fe 3 –LDH/NF and Co 1 Fe 3 –LDH/NF (Figure c), , and the relative area ratios of Fe 2+ to Fe 3+ were about 1:0.67 for Pd/Co 1 Fe 3 –LDH/NF and 1:0.79 for Co 1 Fe 3 –LDH/NF, suggesting the slight reduction of Fe species after loading Pd nanoparticles onto Co 1 Fe 3 –LDH/NF. The results indicated that Pd transferred electrons to Co and Fe in the LDH support, which was evidence of the strong interaction of Pd nanoparticles with the LDH substrate.…”
Section: Resultsmentioning
confidence: 91%
“…As illustrated in Fig. 5(e), in the absence of glucose, the redox peak of Ni appears for Au300 Ni Foam, while a small oxidation peak, probably corresponding to Au → AuOH, appears near 0 V. 41 The shapes of CV curves change significantly when glucose is present, with all three samples showing sharp oxidation peaks in negative scans. The order of the magnitude of the positions of the oxidation peaks for the three samples is Au300 Cu Foam < Au300 Ni Foam < Au300 Fe Foam.…”
Section: Resultsmentioning
confidence: 81%
“…According to previous literature, this pair of peaks is the redox peak of Au 0 with Au 1+ (ref. 41). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Such a Janus MnO 2 -NiFe air electrode endowed the zinc-air battery with better cycling stability and energy efficiency than the bare MnO 2 and NiFe-LDHs electrodes, as illustrated in Figure 14D. In another interesting example, a bifunctional electrocatalyst: Fe 3 O 4 /Au/CoFe-LDH with sandwich structured, was used for the hydrogen evolution reaction and the electrocatalytic glucose oxidation reaction (GOR) [219]. The combination of structural characterizations with electrochemical characterizations revealed that Fe 3 O 4 and CoFe-LDHs played key roles in catalyzing the HER, whereas metallic Au was responsible for the GOR, Figure 14E.…”
Section: Applications Of Ldhs-based Bifunctional Electrocatalystsmentioning
confidence: 99%